Stability and change in health behaviours as predictors for disability pension: a prospective cohort study of Swedish twins - Alexanderson Kristina; Narusyte Jurgita; Ropponen Annina; Svedberg Pia (BMC, 2011)
Abstract Background Stability or changes of health behaviours have not been studied in association with incidence of disability pension (DP). The aims were to (1) investigate if stability or changes in health behaviours predict DP due to musculoskeletal diagnosis (MSD), (2) to evaluate if an association exists for DP in general, and (3) after taking familial confounding into account. Methods The study sample was 16,713 like-sexed twin individuals born in Sweden between 1935-1958 (6195 complete twin pairs) who had participated in two surveys 25 years apart, were alive, and not pensioned at the time of the latest survey. Cox proportional hazards analysis was used to assess the associations (hazard ratios (HR) with 95% confidence intervals (CI)) between stability and change in health behaviours (physical activity, tobacco and alcohol use, body mass index (BMI)), and number of pain locations collected at two time points 25 years apart and the incidence of DP until 2008. Results During the follow-up, 1843 (11%) individuals were granted DP with 747 of these due to MSD. A higher proportion of women were granted DP than men. Increase in BMI and stable use of tobacco products were predictors for DP due to MSD (HR 1.21-1.48) and DP in general (HR 1.10-1.41). The stability in the frequency of physical activity and increased frequency of physical activity were protective factors for DP due to MSD only when accounting for familial confounding. However, the number of pain locations (stability, increase, or decrease) was the strongest predictor for future DP due to MSD (HR 3.69, CI 2.99-4.56) and DP in general (HR 2.15, CI 1.92-2.42). In discordant pair analysis, the HRs for pain were lower, indicating potential familial confounding. Conclusions Health behaviours in adulthood, including an increase in pain locations were associated with the incidence of DP. The association between physical activity and DP was especially related to adulthood choices or habits, i.e., the individual decision about frequency of exercising. Thus, it is important to e.g. increase public awareness of the potential beneficial effects of exercise throughout life to avoid permanent exclusion from the labour market for medical reasons.